Methane Emissions From the Baltimore‐Washington Area Based on Airborne Observations: Comparison to Emissions Inventories. Issue 16 (20th August 2018) - Ren, Xinrong; Salmon, Olivia E.; Hansford, Jonathan R.; Ahn, Doyeon; Hall, Dolly; Benish, Sarah E.; Stratton, Phillip R.; He, Hao; Sahu, Sayantan; Grimes, Courtney; Heimburger, Alexie M. F.; Martin, Cory R.; et al.
Abstract: Urban areas are responsible for a substantial fraction of anthropogenic emissions of greenhouse gases (GHGs) including methane (CH4 ), with the second largest anthropogenic direct radiative forcing relative to carbon dioxide (CO2 ). Quantification of urban CH4 emissions is important for establishing GHG mitigation policies. Comparison of observation‐based and inventory‐based urban CH4 emissions suggests possible improvements in estimating CH4 source emissions in urban environments. In this study, we quantify CH4 emissions from the Baltimore‐Washington area based on the mass balance aircraft flight experiments conducted in Winters 2015 and 2016. The field measurement‐based mean winter CH4 emission rates from this area were 8.66 ± 4.17 kg/s in 2015 and 9.14 ± 4.49 kg/s in 2016, which are 2.8 times the 2012 average U.S. GHG Inventory‐based emission rate. The observed emission rate is 1.7 times that given in a population‐apportioned state of Maryland inventory. Methane emission rates inferred from carbon monoxide (CO) and CO2 emission inventories and observed CH4 /CO and CH4 /CO2 enhancement ratios are similar to those from the mass balance approach. The observed ethane‐to‐methane ratios, with a mean value of 3.3% in Winter 2015 and 4.3% in Winter 2016, indicate that the urban natural gas system could be responsible for 40–60% of total CH4 emissions from this area. Landfills also appear to be a major contributor, providing 25 ± 15% of the total emissions for the region. Our study suggests there are grounds to reexamine the CH4 emissions estimates for the Baltimore‐Washington area and to conduct flights in other seasons. Plain Language Summary: In this study methane emission rates were estimated for the Baltimore‐Washington region based on airborne observations. The inferred methane emission rate is greater than the national greenhouse gas inventory by a factor of 2.8. Reconciliation of the wide range of CH4 emissions estimates from landfills and the natural gas system is necessary. Key Points: An aircraft observation‐based estimate indicates a mean CH4 emission rate of 8.8 ± 2.1 kg/s for the Baltimore‐Washington region CH4 emission rates in the national and MD GHG inventories for this area are factors of 2.8 and 1.7 lower than observed, respectively Reconciliation of the wide range of CH4 emissions estimates from landfills and the natural gas system is necessary